Effect of imidization process on the performance of PI/nano-Al2O3 three layer composite film. Issue 4 (3rd July 2017) - Liu, Lizhu; He, Hongju; Weng, Ling; Zhang, Xiaorui
Abstract : Purpose: The purpose of this paper was to comprehensively understand the effects of imidization process on the structure and properties of polyimide (PI) films through the preparation and characterization of a variety of PI/aluminium oxide (Al2 O3 ) nanocomposite films by using several imidization-based strategies. Design/methodology/approach: Poly(amic acid) (PAA) containing different amounts of inorganic materials (namely, 0 Wt.%, 4 Wt.%, 8 Wt.%, 12 Wt.% and 16 Wt.%) was synthesized by using pyromellitic dianhydride and 4, 4-diaminodiphenyl ether as raw material and N, N-dimethylacetamide as solvent. Subsequently, the solution obtained was casted on a glass substrate and dried by the means of various curing processes. The micro-structure, Fourier transform–infrared spectral features, breakdown field strength, dielectric properties and the corona-resistant time parameters of films were achieved. Findings: The imidization process influences substantially the properties of composite films. Therefore, as the imidization rate is increased, the corona-resistant time and the electrical breakdown strength of composite films are also improved, while the dielectric constant faces a+ decreasing. Research limitations/implications: In this paper, the impact of imidization process on the performance of PI/nano-Al2 O3 three-layered composite film is reported. However, there are multiple factors governing these systems (such as, interlayer thickness ratio and humidity), which are not discussed herein. Originality/value: The current study expounds the relationship between imidization ratios as well as the effect of imidization ratio on the performance of the film.